KENDALA PENYIDIK PPNS DALAM MELAKSANAKAN PENYIDIKAN TINDAK PIDANA KEIMIGRASIAN - Hanna Yuanitha (Unissula, 2019)
The process of investigation against perpetrators of violations of immigration laws is done based on the provisions in The Code Of Criminal Procedure as a lex generalis and Immigration laws as the lex specialists. The method used is the approach of the juridical sociological approach. Juridical is examines the concept of juridical normative showteam or legislation, and empirical which is reviewed on the fact that there are against the implementation of the investigation. The technique of collection data through interviews and research taken from good libraries with books, legislation, papers, previous research results, or from documents. Analysis Data using qualitative analysis, that outlines the data in the form of regular expressions, logical, and effective. The results showed that by 2013 the investigating Immigration Office civil servant class I Semarang have conducted investigation on foreign nationals In 2014 has been carrying out investigation on 10 (ten) cases of illicit immigration and deportation against the 10 (ten) foreign nationals. In the period 2015 as 6 (six) foreigners on deportation after committing immigration offences is proven. While in 2016, in the period January to September with the Immigration Office class I Semarang deport four (4) foreign nationals to their country.